Not the Israel of My Elementary School: An Exploration of Jewish-Canadian Secondary Students' Attempts to Process Morally Complex Israeli Narratives. Issue 3 (4th May 2017) - Reingold, Matt
ABSTRACT: The following article presents data from a mixed-methods practitioner research study that focuses on understanding how Jewish secondary students learned about controversial topics in Israel's history and how these topics impacted their connection to the country. The responses that were provided by the students showed that the material forced students to conceptualize Israel in new ways and that the material— learning from Palestinian and Israeli texts about events that happened in 1947 and 1948—was disruptive to their preconceived notions of Israel. With the passing of time, the students were able to reflect on the real difficulty they had with learning about the topics but were able to synthesize the disruption into their Israel narrative to arrive at a new understanding. The integration of this new material into existing schema is understood within the context of dangerous memories, and how learning about controversial moments in nationalist narratives can impact the way students learn and relate to a topic. A further finding was that some students expressed resentment at previous educational experiences for not being fully transparent about historical events.